1999
DOI: 10.1002/(sici)1097-4644(19990315)72:4<558::aid-jcb11>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced expression of MHC-linked HSP70 genes in lymphocytes varies at the single-cell level

Abstract: The expression of MHC-linked heat shock protein 70 (HSP70) genes HSP70-1 and HSP70-2 has been studied in human and rat lymphocytes and Concanavalin A (con A)-induced lymphoblasts by in situ hybridization and flow cytometry. In in vitro experiments transcripts of these genes were observed only after heat shock, and mitogen stimulation per se did not lead to induction. Heat shock-induced expression of HSP70-1 and HSP70-2 mRNA varied at the single-cell level. The fraction of HSP70-positive lymphocytes increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…high fever, led to a 3-fold increase in HSP70 expression. A similar induction of HSP70 in heat stressed human lymphocytes was recently reported by others (Dressel & Gunther, 1999). We could show that this HSP70 induction is strongly impaired when the Gln concentration in the medium is reduced.…”
Section: Discussionsupporting
confidence: 90%
“…high fever, led to a 3-fold increase in HSP70 expression. A similar induction of HSP70 in heat stressed human lymphocytes was recently reported by others (Dressel & Gunther, 1999). We could show that this HSP70 induction is strongly impaired when the Gln concentration in the medium is reduced.…”
Section: Discussionsupporting
confidence: 90%
“…The advantage of single-cell analysis is that population variability can be assessed. It has been shown that cell populations respond to the environment in ways often not predicted by measurement of the mean response, dispelling the myth of the 'average cell' (Zhao, 1997;Dressel & Gunther, 1999;Levsky & Singer, 2003). In vivo single-cell measurement allows one to probe fundamental questions about intercellular variability and what governs it.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of single coenobia or cell analysis over whole population analysis is that population variability can be assessed. This analysis is important because it has been shown that cell populations respond to the environment in ways often not predicted by measurement of the average response (Zhao 1997, Dressel and Gunther 1999, Levsky and Singer 2003).…”
Section: Band Assignments and Data Analysismentioning
confidence: 99%